Bahasa Indonesia: Bahasa Indonesia - Akhmad Rofii Damyati; Ridwan, Ridwan (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2024)
This article examines the development of the negative framing of Islam as an intolerant religion within contemporary discourse, particularly in Western media. Through a historical and analytical approach, this study reveals that accusations of intolerance towards Islam often overlook the rich intellectual history of Islam, characterized by a diversity of thought and openness to knowledge from other civilizations. Since the classical era, Muslim scholars such as Al-Khwarizmi and Ibn Sina have demonstrated intellectual tolerance by adapting and integrating foreign knowledge through the process of "Islamization" of knowledge. Furthermore, the article explores the impact of Western colonialism and postcolonial global political dynamics in shaping negative perceptions of Islam, leading to inaccurate and harmful stereotypes. By tracing these historical and contemporary complexities, this research aims to address existing misconceptions and offer a more balanced understanding of the concept of tolerance within the Islamic tradition. Keywords: Intellectual tolerance, Image of intolerance, Islamization of knowledge, Western colonialism, Futuhat Islamiyah